THE PROBLEMS OF TEACHING LANGUAGE AND LITERATURE (Proceedings of International Educators Conference, 2023)
Language and Literature are not just a part of human expression but also of life, culture and history. No wonder then the teaching methods proposed by academic scientists are only catalysts that can supplement teaching-learning process, which is independent to a teacher and is subjected to change based on place and time. Orthodox religion and liberal language are always paradoxical to each other however the ubiquity of English language is changing the perspective of even conservative countries. There are the linguistic, cultural, educational, political and personal challenges that Uzbek students face while learning English language. This paper is my sincere attempt to incubate my teaching-learning experience and to provide a preparatory glance for those who wish to see their career prosperity in the Uzbek world.